Inovasi dan Strategi Guru IPA di SMK Menghadapi Kendala dalam Pembelajaran Online di Masa Pandemi COVID-19 - Diana Zulyetti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the innovations and strategies carried out by science teachers at SMK Negeri 3 Payakumbuh in carrying out online learning in the atmosphere of the COVID-19 pandemic. The method used is descriptive-quantitative through the distribution of questionnaires and interviews with science teachers at SMK Negeri 3 Payakumbuh. The results showed that teacher innovation with high criteria was at the preparation stage (88.02%) and learning implementation (79.16%) and teacher innovation was very high at the learning evaluation stage (89.58%). Teachers also carry out planning strategies, tactics and pattern strategies in dealing with various obstacles in implementing online science learning. In conclusion, science teachers at SMK Negeri 3 Payakumbuh innovate at every stage of online learning. Keywords: Innovation, Science Vocational High School Learning, Strategy